Electronic influence of β‐diketonato‐type ligands on the coordination of 1, 5‐cyclooctadiene to palladium(II) as defined by `Venus fly trap' geometric parameters. (1st January 2013) - Hill, Tania N.; Roodt, Andreas; Steyl, Gideon
<x xml:space="preserve">Abstract</x> A range of single‐crystal structures of the type [Pd(cod)(LL′‐Bid)]A, where LL′‐Bid = acetylacetonato (acac), thenoyltrifluoroactetonato (thtfac) and hexafluoroacetylacetonato (hfacac), and A = tetrafluoroborate (BF4−) and hexafluorophosphate (PF6−), are reported. The complexes [Pd(cod)(acac)]PF6 (I), [Pd(cod)(thtfac)]PF6 (III), [Pd(cod)(thtfac)]BF4 (IV) and [Pd(cod)(hfacac)]PF6 (V) are isostructural in the monoclinic space group P21/c. The influence of the variation of the β‐diketonato‐type ligands on the coordination geometry of cis, cis‐1, 5‐cycloocta‐1, 5‐diene (cod) was investigated and found that no significant changes to the Pd—C and C=C bond distances were observed. The `Venus fly trap' parameters vary by 7.8° for the `jaw' angle (ψ), while the `bite' angle (χ) remains virtually constant.